Accurately detecting happy facial expressions associates with perceptions of flirtatiousness. (April 2023) - Bibby, Emily S.; McKinnon, Allison M.; Shaw, Michael; Mattson, Richard E.
Emotional facial expressions are relevant to flirtation because they provide information on an individual's intentions or motivations. Individual differences in the ability to accurately detect and discriminate between normative facially expressed emotions could lead to misperceptions of the level of sexual interest being conveyed, which has been linked to sexual assault and harassment. To explore this notion, we recruited a national sample of college aged male and female participants ( N = 219) who completed a novel facial expression recognition task used to detect accuracy in processing facial emotions of happiness, surprise, anger, and disgust. Participants also viewed multiple video clips of blind dates between two different-sex participants and rated each partner on their degree of flirtatiousness. Consistent with predictions, we found that individuals who misidentified other facial emotions for happiness appeared to overestimate flirtation. Though not predicted, participants who failed to accurately identify happy faces also overestimated flirtation, whereas individuals who took longer to respond to emotional facial expressions and misidentified an emotion as conveying happiness made greater errors in perceptions of flirtatiousness. Overall, these findings suggest that individual differences in the ability to detect and discriminate happiness through facial expressions are relevant to misperceptions of flirtatious behavior, and more broadly illuminates the role of basic emotion recognition on perceptions of flirtatiousness.